Preparation method of low-density super-hydrophobic glass fiber aerogel felt
By using low-density glass fiber needle felt and superhydrophobic modification treatment technology in aerogel composite materials, low-density ultrahydrophobic glass fiber aerogel felt was prepared, which solved the problem that existing materials could not meet the needs of light weight and ultra-high hydrophobic properties in special industries, and achieved high-performance aerogel felt materials.
Patent Information
- Application Number
- CN202510007098.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-03-28
AI Technical Summary
Existing aerogel composites cannot meet the needs of light weight and ultra-high hydrophobic properties in special industries such as ships.
Low-density ultra-hydrophobic glass fiber aerogel felt is used as the substrate, and low-density ultra-hydrophobic glass fiber aerogel felt is prepared by spraying composite glue liquid, hot pressing curing, aging-superhydrophobic modification treatment and supercritical drying.
The prepared aerogel felt has the advantages of fire resistance, flame retardancy, and environmental friendliness, to meet the needs of special industries.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano aerogel material preparation, and in particular to a method for preparing a low-density super-hydrophobic glass fiber aerogel felt. Background Art
[0002] Aerogel is a form of solid matter and a new type of material with a nanoporous structure. It has excellent properties such as extremely low density, high specific surface area, and low thermal conductivity, and has broad application prospects in the fields of thermal insulation, adsorption, and catalysis. Silica aerogel is a solid material with a three-dimensional nanoporous structure composed of nanoparticles. It has the characteristics of chemical inertness, thermal insulation, sound insulation, vibration absorption, and selective adsorption. It has been widely used in many fields such as industrial thermal insulation and energy saving, power battery safety and fire prevention, automobile energy saving and sound insulation, building energy saving, spacecraft thermal insulation, and refrigerator cold preservation, and has a very broad application potential.
[0003] Aerogel is listed as one of the top 10 hot new materials in the 21st century for its thermal conductivity of 0.026 W / mK, which is lower than the thermal conductivity of still air, extremely light volume density, high specific surface area of 200m2 / g to 1000m2 / g, good thermal insulation performance and environmental protection. The emergence of aerogel can be traced back to 1931, when Steven S. Kistler of the United States used acidic concentration of sodium silicate aqueous solution, dissolved silica with supercritical water, exchanged water in the pores with ethanol, and used supercritical fluid drying technology to make the first real aerogel. However, due to the limitations of scientific research methods at the time, the development of this material did not attract the attention of the scientific community at the time.
[0004] In the 1970s, Stanislaus Teichner of France applied sol-gel chemistry to the preparation of silica aerogels, which promoted the development of aerogel science. In 1983, Berkeley Laboratory replaced ethanol with carbon dioxide supercritical fluid with lower critical temperature and critical pressure as the fluid for supercritical drying, which enabled supercritical drying technology to move towards the practical stage. In 1985, Tewari used carbon dioxide as the supercritical drying medium and successfully dried wet gels, which promoted the commercialization of silica aerogels.
[0005] Aerogel has been around for nearly a hundred years, but its commercial application has not been long. Since 2012, more than a dozen domestic companies have entered the silica aerogel insulation industry. The market competition has become increasingly fierce, and product quality requirements have become higher and higher. At present, aerogel composites are mainly used in thermal pipeline engineering, aerospace, shipbuilding, new energy vehicles and other fields. Since aerogel is a solid material with high porosity, low thermal conductivity and low dielectric constant, these excellent properties make aerogel widely used in more fields and have broad application potential. The volume density of conventional aerogel composites is 180kg / m 3 ~220kg / m 3 , the hydrophobicity is 98%, which cannot meet the needs of some special industries (such as ships) for light weight and ultra-high hydrophobicity of materials. Therefore, it is necessary to develop a light weight and super-hydrophobic aerogel felt to meet the use needs of special industries, thereby expanding its application in more fields, which has important practical significance. Summary of the invention
[0006] The technical problem to be solved by the present invention is to solve the problems existing in the background technology and to solve the requirements of special industries such as ships for light weight and ultra-high hydrophobicity of aerogel composite materials, thereby providing a method for preparing a low-density super-hydrophobic glass fiber aerogel felt. The aerogel felt prepared by this method not only has light weight and ultra-high hydrophobicity, but also has the advantages of fire resistance and flame retardancy, so as to meet the use requirements of special industries for aerogel composite materials. Specifically, it is a method for preparing a low-density super-hydrophobic glass fiber aerogel felt.
[0007] In order to solve the above technical problems, the present invention provides a method for preparing a low-density super-hydrophobic glass fiber aerogel felt, and the preparation method comprises the following steps: S1. Raw material selection: Choose low-density glass fiber mat as the base material, and choose a spacer net that has both spacing and supporting functions; S2. Preparation of sol: The silicon source and the solvent are dispersed in water and hydrolyzed to obtain a mixed sol after hydrolysis; S3. Spray coating: Lay the substrate material selected in step S1 in a spray tank, and then mix the mixed glue prepared in step S2 with the gel catalyst at a ratio of 1: (0.01-0.125) to obtain a composite glue, and finally spray the prepared composite glue evenly on the substrate material through a sprayer to obtain a composite gel material; S4. hot pressing curing: transporting the composite gel material obtained in step S3 to a microwave heating device, starting microwave heating, so that the composite gel material is reacted and gelled into a wet gel felt, then fixing one end of the separator prepared in step S1, straightening the other end and rolling it on a tooling, laying the wet gel felt from the microwave heating device on the separator, and finally rolling the wet gel and the separator on the tooling synchronously to obtain a composite wet gel semi-finished product; S5. Aging - super-hydrophobic modification: The composite wet gel semi-finished product obtained in step S4 is first aged, the composite wet gel semi-finished product after aging is treated with a hydrophobic agent, and then subjected to super-hydrophobic modification, and a composite wet gel finished product is obtained after modification; S6. Drying treatment: The composite wet gel product obtained in step S5 is placed in a supercritical drying kettle, and after drying treatment, an aerogel felt material is obtained.
[0008] Furthermore, in the method for preparing a low-density super-hydrophobic glass fiber aerogel felt according to the present invention, in step S1, the raw material selection stage, the low-density glass fiber felt is selected to have a volume density of 60 kg / m 3 ~130kg / m 3 A glass fiber needle felt substrate with a thermal conductivity of no more than 0.035 W / (m·K) is used as the composite matrix.
[0009] Furthermore, a method for preparing a low-density super-hydrophobic glass fiber aerogel felt according to the present invention is adopted, wherein the low-density glass fiber felt is made of glass fiber chopped hair needle felt with a diameter of 10 μm to 20 μm and a length of 50 mm to 120 mm and is subjected to edge locking treatment.
[0010] Furthermore, in the method for preparing a low-density super-hydrophobic glass fiber aerogel felt described in the present invention, in the raw material selection stage of step S1, the separator is selected from any one of a polyethylene plastic mesh, a polyester spiral mesh, a polyester grid mesh or a steel wire mesh.
[0011] Furthermore, a method for preparing a low-density super-hydrophobic glass fiber aerogel felt described in the present invention is adopted. In the sol preparation stage of step S2, the silicon source is selected from at least one of ethyl orthosilicate, methyl orthosilicate, and their polymers, with a silicon content of 37% to 52% and a purity of more than 99%; and the solvent is selected from a mixture of one or two of methanol or ethanol mixed in any proportion, with a purity of more than 99.9%; wherein the molar ratio of the silicon source, the solvent and water is 1:(24 to 138):(0.74 to 2.22); during the hydrolysis process, a hydrolysis catalyst needs to be added to adjust the pH of the hydrolysis solution, and to control the hydrolysis reaction time and the hydrolysis reaction temperature.
[0012] Furthermore, in a method for preparing a low-density super-hydrophobic glass fiber aerogel felt described in the present invention, the hydrolysis catalyst is selected from at least one of hydrochloric acid, oxalic acid, phosphoric acid, nitric acid or boric acid, the pH of the hydrolysis solution is controlled at 3 to 7, the hydrolysis reaction time is controlled at 1 h to 10 h, and the hydrolysis reaction temperature is controlled at 20°C to 60°C.
[0013] Furthermore, a method for preparing a low-density super-hydrophobic glass fiber aerogel felt described in the present invention is adopted. In the spray coating stage of step S3, the gel catalyst is selected from at least one of ammonia water, ammonium fluoride, ethylenediamine, sodium hydroxide or tetraethoxyammonium hydroxide; the mixed glue and the gel catalyst are evenly mixed in a weight ratio of 1: (0.01-0.05) to obtain a composite glue, and finally the prepared composite glue is evenly sprayed on the substrate raw material through a sprayer, the spray flow rate and the production line belt speed are controlled to keep the glue absorption ratio between 1.1 and 1.2, and the time for composite formation of wet gel is controlled to be between 3min and 15min.
[0014] Furthermore, a method for preparing a low-density super-hydrophobic glass fiber aerogel felt according to the present invention is adopted, which is characterized in that: in the hot pressing and curing stage of step S4, the composite gel material is transported to the front end of the first cavity in the microwave heating equipment, microwave heating is started, and the microwave start-up power and the production line belt speed are controlled, and the microwave start-up power can be 1 / 6 to 2 / 3 of the total microwave power.
[0015] Furthermore, a method for preparing a low-density super-hydrophobic glass fiber aerogel felt described in the present invention is adopted. In the aging-super-hydrophobic modification treatment stage of step S5, the aging treatment time is 8h~48h, and the hydrophobic modification time is 4h~24h, the hydrophobic modification temperature is 45°C~60°C, and during the aging treatment and hydrophobic modification treatment process, it is necessary to start a circulation pump to continuously circulate the composite wet gel semi-finished product to promote the full reaction of the composite gel material; wherein the hydrophobic agent is selected from at least one of hexamethyldisilazane, dimethyldiethoxysilane or dimethyldimethoxysilane.
[0016] Furthermore, the method for preparing a low-density super-hydrophobic glass fiber aerogel felt according to the present invention is adopted. In the drying treatment stage of step S6, under a supercritical state, carbon dioxide is used as a drying medium, the temperature in the drying kettle is controlled to be 40°C to 75°C, the pressure is 10Mpa to 18Mpa, and the carbon dioxide flow rate is 2m 3 / h~4m 3 / h, the drying time is 4h to 16h; after drying, an aerogel felt material is obtained, and the volume density of the aerogel felt material is not more than 170 kg / m 3 , the hydrophobicity is not less than 99.6%.
[0017] The method for preparing a low-density super-hydrophobic glass fiber aerogel felt according to the present invention has the following beneficial effects compared with the prior art: a low-density glass fiber needle-punched felt substrate is used as a composite substrate after edge locking treatment, which has the advantages of lighter weight and lower unit price compared with conventional substrates, and its edge is tight and not easy to delaminate; in the hot pressing curing stage, a microwave gel curing process is used, which is compared with conventional hot water line gel curing, not only the work efficiency can be improved by 2 to 3 times, but also the labor can be reduced by about 4 to 6 people, which greatly reduces the processing cost, and the microwave gel curing technology can make the sol quickly and evenly heated, effectively regulate the microscopic pore structure, and effectively solve the problem of uneven heating by traditional hot water heating; due to the traditional hot water heating method, the contact position with the belt is heated quickly, and the internal part of the material is heated very slowly, resulting in surface gelation while the internal part has not yet gelled, and the gelation time needs to be extended, the gel quality is greatly affected by the ambient temperature, and the gelation efficiency is low. The product prepared by microwave gel curing has more stable and excellent performance; after microwave gel curing, the aging-super-hydrophobic modification process is used, so that the material can be given super-hydrophobic properties. The performance of conventional aerogel composite felt cannot meet the requirements of some special fields for low volume density and ultra-high hydrophobic performance of aerogel composite felt. The volume density of the aerogel felt prepared by the method of the present invention is not more than 170kg / m 3 The hydrophobicity is not less than 99.6%. The volume density of the aerogel felt prepared by conventional methods is 180kg / m 3 ~220kg / m 3 The hydrophobicity is less than 98%, which can meet the requirements of special industries such as ships for low volume density and ultra-high hydrophobicity of aerogel composite felt. At the same time, it has the advantages of fire resistance, flame retardancy and environmental friendliness, and can be used for aerogel composite materials with a volume density of no more than 170 kg / m 3 , ships with a water repellency greater than 99% and other fields where heat insulation, flame retardancy, shock resistance and sound absorption are required.
[0018] It can be seen that the preparation method of the present invention has the advantages of short production cycle and low production cost, and is suitable for industrial production. The prepared aerogel felt product is successfully prepared in batches with a volume density of no more than 170 kg / m 3 The hydrophobicity is over 99.6%. It also has the advantages of fire resistance, flame retardancy and environmental friendliness. It can meet the use needs of special industries for aerogel composite materials and can bring technological breakthroughs and economic benefits to related industries. DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0020] This embodiment provides a method for preparing a low-density super-hydrophobic glass fiber aerogel felt, and the preparation method comprises the following steps: S1. Raw material selection: select bulk density between 60 and 80 kg / m 3 A glass fiber needle felt substrate with a thermal conductivity of no more than 0.035 W / (m·K) is used as the composite matrix, wherein the glass fiber needle felt substrate is made of a glass fiber chopped hair needle felt substrate with a diameter of 10 to 20 μm and a length of 50 to 80 mm and is subjected to edge locking treatment; at the same time, a polyester spiral mesh having both a spacing and a supporting function is selected for standby; S2. Preparation of sol: Select ethyl orthosilicate with a silicon content of 37% to 52% and a purity of more than 99% as a silicon source, and select ethanol with a purity of more than 99.9% as a solvent, and mix them according to silicon: alcohol: water = 1:88:0.79 for hydrolysis, and add hydrochloric acid to adjust the pH value between 3 and 7, then turn on the stirring device for stirring, control the hydrolysis reaction time at 4 to 6 hours, and control the hydrolysis reaction temperature at 35 to 45 ° C. After hydrolysis, a mixed glue solution is obtained; S3. Spray coating: the substrate material selected in step S1 is laid in a spray tank, and then the mixed glue prepared in step S2 is mixed with the gel catalyst at a ratio of 1:0.03 to obtain a composite glue, wherein the gel catalyst is ammonia water, and finally the prepared composite glue is evenly sprayed on the substrate material through a sprayer, the spray flow rate and the production line belt speed are controlled to keep the glue absorption ratio at 1.1 to 1.2, and the time for composite formation of wet gel is controlled at 3 min to 15 min to obtain a composite gel material; S4. Hot pressing curing: transport the composite gel material obtained in step S3 to the front end of the first cavity in the microwave heating equipment, quickly start microwave heating, adjust the microwave opening degree to 50 / 50 / 45 / 45 / 40 / 35 / 30, and adjust the belt speed after the temperature of the entire production line is stable, so that the composite gel material is reacted and gelled into a wet gel felt, and then fix one end of the partition net prepared in step S1, straighten the other end and roll it on the tooling, and lay the wet gel felt from the microwave heating equipment on the partition net, and finally roll the wet gel and the partition net on the tooling synchronously to obtain a composite wet gel semi-finished product, and hoist it to the next step; S5. Aging-super-hydrophobic modification: The composite wet gel semi-finished product obtained in step S4 is first aged for 24 hours, and an appropriate amount of hydrophobic agent is added to the composite wet gel semi-finished product after aging. The hydrophobic agent is hexamethyldisilazane, and then super-hydrophobic modification is performed. The hydrophobic modification time is 16 hours and the hydrophobic modification temperature is 45°C. During the aging-hydrophobic modification process, a circulation pump needs to be turned on to circulate the solution to ensure sufficient reaction. After the modification, a composite wet gel finished product is obtained; S6. Drying treatment: The finished composite wet gel obtained in step S5 is placed in a supercritical drying kettle. Under the supercritical state, carbon dioxide is used as the drying medium. The temperature in the drying kettle is controlled to be 40-45°C, the pressure is 10Mpa, and the carbon dioxide flow rate is 2m 3 / h, the drying time is 4 to 8h; after drying, an aerogel felt material is obtained, and the solvent in the wet gel is taken out by carbon dioxide under a supercritical state, thereby drying and preparing a low-density super-hydrophobic glass fiber aerogel felt, and the volume density, thermal conductivity and water repellency performance of the low-density super-hydrophobic aerogel felt are tested. The volume density of the aerogel felt material is not more than 170 kg / m 3 , the hydrophobicity is not less than 99.6%.
[0021] Implementation Case 2 This embodiment provides a method for preparing a low-density super-hydrophobic glass fiber aerogel felt, and the preparation method comprises the following steps: S1. Raw material selection: Select bulk density between 70 and 100 kg / m 3 A glass fiber needle felt substrate with a thermal conductivity of no more than 0.035 W / (m·K) is used as the composite matrix, wherein the glass fiber needle felt substrate is made of a glass fiber chopped hair needle felt substrate with a diameter of 10 to 20 μm and a length of 70 to 90 mm and is subjected to edge locking treatment; at the same time, a polyester spiral mesh having both spacing and supporting functions is selected for standby; S2. Preparation of sol: methyl orthosilicate with a silicon content of 37% to 52% and a purity of more than 99% is selected as a silicon source, and ethanol with a purity of more than 99.9% is selected as a solvent, and the mixture is hydrolyzed according to the ratio of silicon: alcohol: water = 1:73:0.79, and oxalic acid is added to adjust the pH value between 3 and 7, and then the stirring device is turned on for stirring, the hydrolysis reaction time is controlled at 5 to 8 hours, and the hydrolysis reaction temperature is controlled at 40 to 50 ° C, and a mixed glue solution is obtained after hydrolysis; S3. Spray coating: Lay the substrate material selected in step S1 in a spray tank, then mix the mixed glue prepared in step S2 with the gel catalyst at a ratio of 1:0.025 to obtain a composite glue, wherein the gel catalyst is sodium hydroxide, and finally spray the prepared composite glue evenly on the substrate material through a sprayer, control the spray flow rate and the production line belt speed, keep the glue absorption ratio at 1.1 to 1.2, and control the time for composite formation of wet gel at 3 min to 15 min to obtain a composite gel material; S4. Hot pressing curing: transport the composite gel material obtained in step S3 to the front end of the first cavity in the microwave heating equipment, quickly start microwave heating, adjust the microwave opening degree to 60 / 60 / 55 / 55 / 45 / 35 / 30, and adjust the belt speed after the temperature of the entire production line is stable, so that the composite gel material is reacted and gelled into a wet gel felt, and then fix one end of the partition net prepared in step S1, straighten the other end and roll it on the tooling, and lay the wet gel felt from the microwave heating equipment on the partition net, and finally roll the wet gel and the partition net on the tooling synchronously to obtain a composite wet gel semi-finished product, and hoist it to the next step; S5. Aging-super-hydrophobic modification: The composite wet gel semi-finished product obtained in step S4 is first aged for 24 hours, and an appropriate amount of hydrophobic agent is added to the composite wet gel semi-finished product after aging, wherein the hydrophobic agent is hexamethyldisilazane, and then super-hydrophobic modification is performed for 16 hours at a hydrophobic modification temperature of 50° C. During the aging-hydrophobic modification process, a circulating pump needs to be turned on to circulate the solution to ensure sufficient reaction, and a composite wet gel finished product is obtained after modification; S6. Drying treatment: The finished composite wet gel obtained in step S5 is placed in a supercritical drying kettle. Under supercritical conditions, carbon dioxide is used as the drying medium. The temperature in the drying kettle is controlled to be 45-50°C, the pressure is 15 MPa, and the carbon dioxide flow rate is 2.5 m 3 / h, the drying time is 8 to 12h; after drying, an aerogel felt material is obtained, and the solvent in the wet gel is taken out by carbon dioxide in a supercritical state, thereby drying and preparing a low-density super-hydrophobic glass fiber aerogel felt, and the volume density, thermal conductivity and water repellency performance of the low-density super-hydrophobic aerogel felt are tested. The volume density of the aerogel felt material is not more than 170 kg / m 3 , the hydrophobicity is not less than 99.6%.
[0022] Implementation Case 3 This embodiment provides a method for preparing a low-density super-hydrophobic glass fiber aerogel felt, and the preparation method comprises the following steps: S1. Raw material selection: Select bulk density between 80 and 100 kg / m 3A glass fiber needle felt substrate with a thermal conductivity of no more than 0.035 W / (m·K) is used as the composite matrix, wherein the glass fiber needle felt substrate is made of a glass fiber chopped hair needle felt substrate with a diameter of 10 to 20 μm and a length of 80 to 110 mm and is subjected to edge locking treatment; at the same time, a polyester spiral mesh having both a spacing and a supporting function is selected for standby; S2. Preparation of sol: Select ethyl orthosilicate with a silicon content of 37% to 52% and a purity of more than 99% as the silicon source, and select methanol with a purity of more than 99.9% as the solvent, and mix them according to silicon: alcohol: water = 1:64:0.79 for hydrolysis, and add boric acid to adjust the pH value between 3 and 7, then turn on the stirring device for stirring, control the hydrolysis reaction time at 7 to 9 hours, and control the hydrolysis reaction temperature at 45 to 55 ° C. After hydrolysis, a mixed glue solution is obtained; S3. Spray coating: the substrate material selected in step S1 is laid in a spray tank, and then the mixed glue prepared in step S2 is mixed with the gel catalyst at a ratio of 1:0.025 to obtain a composite glue, wherein the gel catalyst is tetraethoxyammonium hydroxide, and finally the prepared composite glue is evenly sprayed on the substrate material through a sprayer, the spray flow rate and the production line belt speed are controlled to keep the glue absorption ratio at 1.1 to 1.2, and the time for composite formation of wet gel is controlled at 3 min to 15 min to obtain a composite gel material; S4. Hot pressing curing: transport the composite gel material obtained in step S3 to the front end of the first cavity in the microwave heating equipment, quickly start microwave heating, adjust the microwave opening degree to 50 / 50 / 45 / 45 / 40 / 35 / 30, and adjust the belt speed after the temperature of the entire production line is stable, so that the composite gel material is reacted and gelled into a wet gel felt, and then fix one end of the partition net prepared in step S1, straighten the other end and roll it on the tooling, and lay the wet gel felt from the microwave heating equipment on the partition net, and finally roll the wet gel and the partition net on the tooling synchronously to obtain a composite wet gel semi-finished product, and hoist it to the next step; S5. Aging-super-hydrophobic modification: The composite wet gel semi-finished product obtained in step S4 is first aged for 24 hours, and an appropriate amount of hydrophobic agent is added to the composite wet gel semi-finished product after aging. The hydrophobic agent is dimethyldiethoxysilane, and then super-hydrophobic modification is performed. The hydrophobic modification time is 16 hours and the hydrophobic modification temperature is 55° C. During the aging-hydrophobic modification process, a circulation pump needs to be turned on to circulate the solution to ensure sufficient reaction. After the modification treatment, a composite wet gel finished product is obtained; S6. Drying treatment: The finished composite wet gel obtained in step S5 is placed in a supercritical drying kettle. Under supercritical conditions, carbon dioxide is used as the drying medium. The temperature in the drying kettle is controlled to be 55°C to 65°C, the pressure is 15Mpa, and the carbon dioxide flow rate is 3m 3 / h, the drying time is 12 to 15h; after drying, an aerogel felt material is obtained, and the solvent in the wet gel is taken out by carbon dioxide under a supercritical state, thereby drying and preparing a low-density super-hydrophobic glass fiber aerogel felt, and the volume density, thermal conductivity and water repellency properties of the low-density super-hydrophobic aerogel felt are tested. The volume density of the aerogel felt material is not more than 170 kg / m 3 , the hydrophobicity is not less than 99.6%.
[0023] Implementation Case 4 This embodiment provides a method for preparing a low-density super-hydrophobic glass fiber aerogel felt, and the preparation method comprises the following steps: S1. Raw material selection: Select bulk density between 100 and 120 kg / m 3 A glass fiber needle felt substrate with a thermal conductivity of no more than 0.035 W / (m·K) is used as the composite matrix, wherein the glass fiber needle felt substrate is made of a glass fiber chopped hair needle felt substrate with a diameter of 10 to 20 μm and a length of 110 to 120 mm and is processed by edge locking; at the same time, a steel wire mesh with both spacing and supporting functions is selected for standby; S2. Preparation of sol: Select ethyl orthosilicate with a silicon content of 37% to 52% and a purity of more than 99% as the silicon source, and select methanol with a purity of more than 99.9% as the solvent, and mix them according to silicon: alcohol: water = 1:128:0.79 for hydrolysis, and add phosphoric acid to adjust the pH value between 3 and 7, then turn on the stirring device for stirring, control the hydrolysis reaction time at 8 to 10 hours, and control the hydrolysis reaction temperature at 40 to 60 ° C. After hydrolysis, a mixed glue solution is obtained; S3. Spray coating: lay the substrate material selected in step S1 in a spray tank, then mix the mixed glue prepared in step S2 with the gel catalyst at a ratio of 1:0.025 to obtain a composite glue, wherein the gel catalyst is ethylenediamine, and finally spray the prepared composite glue evenly on the substrate material through a sprayer, control the spray flow rate and the production line belt speed, keep the glue absorption ratio at 1.1 to 1.2, and control the time for composite formation of wet gel at 3 min to 15 min to obtain a composite gel material; S4. Hot pressing curing: transport the composite gel material obtained in step S3 to the front end of the first cavity in the microwave heating equipment, quickly start microwave heating, adjust the microwave opening degree to 50 / 50 / 45 / 45 / 40 / 35 / 30, and adjust the belt speed after the temperature of the entire production line is stable, so that the composite gel material is reacted and gelled into a wet gel felt, and then fix one end of the partition net prepared in step S1, straighten the other end and roll it on the tooling, and lay the wet gel felt from the microwave heating equipment on the partition net, and finally roll the wet gel and the partition net on the tooling synchronously to obtain a composite wet gel semi-finished product, and hoist it to the next step; S5. Aging-super-hydrophobic modification: The composite wet gel semi-finished product obtained in step S4 is first aged for 24 hours, and an appropriate amount of hydrophobic agent is added to the composite wet gel semi-finished product after aging. The hydrophobic agent adopts dimethyldimethoxysilane, and then super-hydrophobic modification is performed. The hydrophobic modification time is 16 hours and the hydrophobic modification temperature is 60°C. During the aging-hydrophobic modification process, a circulation pump needs to be turned on to circulate the solution to ensure sufficient reaction. After the modification treatment, a composite wet gel finished product is obtained; S6. Drying treatment: The finished composite wet gel obtained in step S5 is placed in a supercritical drying kettle. Under supercritical conditions, carbon dioxide is used as the drying medium. The temperature in the drying kettle is controlled to be 65-75°C, the pressure is 18Mpa, and the carbon dioxide flow rate is 4m 3 / h, the drying time is 13 to 16h; after drying, an aerogel felt material is obtained, and the solvent in the wet gel is taken out by carbon dioxide under a supercritical state, thereby drying and preparing a low-density super-hydrophobic glass fiber aerogel felt, and the volume density, thermal conductivity and water repellency properties of the low-density super-hydrophobic aerogel felt are tested. The volume density of the aerogel felt material is not more than 170 kg / m 3 , the hydrophobicity is not less than 99.6%.
[0024] The performance of the low-density super-hydrophobic aerogel felt prepared in Examples 1 to 4 and the conventional aerogel felt was tested, and the results are shown in the following table: Low density super hydrophobic glass fiber aerogel felt performance table
[0025] By comparison, it can be seen that the performance indicators of the aerogel felt composite material prepared by the method of the present invention all meet the requirements of thermal conductivity less than or equal to 0.021 W / (m·K) and volume density not greater than 170 kg / m 3 And the use requirement of water repellency above 99.6%.
[0026] In summary, the preparation method of the present invention has the advantages of short production cycle and low production cost, and is suitable for industrial production. The prepared aerogel felt product is successfully prepared in batches through theoretical calculation, experimental verification and small-batch trial production with a volume density of no more than 170 kg / m 3 The hydrophobicity is over 99.6%. It also has the advantages of fire resistance, flame retardancy and environmental friendliness. It can meet the use needs of special industries for aerogel composite materials and can bring technological breakthroughs and economic benefits to related industries.
[0027] Other aspects of the present invention that are not described in detail are all conventional techniques known to those skilled in the art.
[0028] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a low-density super-hydrophobic glass fiber aerogel felt, characterized in that: The preparation method comprises the following steps: S1. Raw material selection: Choose low-density glass fiber mat as the base material, and choose a spacer net that has both spacing and supporting functions; S2. Preparation of sol: The silicon source and the solvent are dispersed in water and hydrolyzed to obtain a mixed sol after hydrolysis; S3. Spray coating: the substrate material selected in step S1 is laid in a spray tank, and then the mixed glue prepared in step S2 is mixed with the gel catalyst at a ratio of 1: (0.01 to 0.125) to obtain a composite glue, and finally the prepared composite glue is evenly sprayed on the substrate material by a sprayer to obtain a composite sol material; S4. hot pressing solidification: transport the composite sol material obtained in step S3 to a microwave heating device, start microwave heating, and make the composite sol material gel into a wet gel felt through reaction, then fix one end of the separator prepared in step S1, straighten the other end and roll it on a tooling, lay the wet gel felt from the microwave heating device on the separator, and finally roll the wet gel and the separator on the tooling synchronously to obtain a composite wet gel semi-finished product; S5. Aging - super-hydrophobic modification: The composite wet gel semi-finished product obtained in step S4 is first aged, the aged composite wet gel semi-finished product is treated with a hydrophobic agent, and then subjected to super-hydrophobic modification to obtain a composite wet gel finished product after modification; S6. Drying treatment: The composite wet gel product obtained in step S5 is placed in a supercritical drying kettle, and after drying treatment, an aerogel felt material is obtained.
2. The method for preparing a low-density super-hydrophobic glass fiber aerogel felt according to claim 1, characterized in that: In the raw material selection stage of step S1, the low-density glass fiber mat substrate is selected with a volume density of 60kg / m 3 ~130kg / m 3 A glass fiber needle felt substrate with a thermal conductivity of no more than 0.035 W / (m·K) is used as the composite matrix.
3. A method for preparing a low-density super-hydrophobic glass fiber aerogel felt according to claim 2, characterized in that: The low-density glass fiber felt is made of glass fiber chopped hair needle felt with a diameter of 10 μm to 20 μm, a length of 50 mm to 120 mm, and a certain component content, and is processed by edge locking.
4. The method for preparing a low-density super-hydrophobic glass fiber aerogel felt according to claim 1, characterized in that: In the raw material selection stage of step S1, the separator is selected from any one of polyethylene plastic mesh, polyester spiral mesh, polyester grid mesh or steel wire mesh.
5. The method for preparing a low-density super-hydrophobic glass fiber aerogel felt according to claim 1, characterized in that: In the sol preparation stage of step S2, the silicon source is selected from at least one of ethyl orthosilicate, methyl orthosilicate, and polymers thereof, with a silicon content of 37% to 52% and a purity of more than 99%; and the solvent is selected from a mixture of one or two of methanol or ethanol in any ratio, with a purity of more than 99.9%; wherein the molar ratio of the silicon source, the solvent and water is 1:(24 to 138):(0.74 to 2.22); during the hydrolysis process, a hydrolysis catalyst needs to be added to adjust the pH of the hydrolysis solution, and to control the hydrolysis reaction time and the hydrolysis reaction temperature.
6. The method for preparing a low-density super-hydrophobic glass fiber aerogel felt according to claim 5, characterized in that: The hydrolysis catalyst is selected from at least one of hydrochloric acid, oxalic acid, phosphoric acid, nitric acid or boric acid, the pH of the hydrolysis solution is controlled at 3-7, the hydrolysis reaction time is controlled at 1h-10h, and the hydrolysis reaction temperature is controlled at 20°C-60°C.
7. The method for preparing a low-density super-hydrophobic glass fiber aerogel felt according to claim 1, characterized in that: In step S3, the gel catalyst is selected from at least one of ammonia water, ammonium fluoride, ethylenediamine, sodium hydroxide or tetraethoxyammonium hydroxide; the mixed glue liquid and the gel catalyst are evenly mixed in a weight ratio of 1: (0.01-0.05) to obtain a composite glue liquid, and finally the prepared composite glue liquid is evenly sprayed on the substrate raw material through a sprayer, and the spray flow rate and the production line belt speed are controlled to keep the glue absorption ratio between 1.1 and 1.2, and the time for composite formation of wet gel is controlled to be 3min to 15min.
8. The method for preparing a low-density super-hydrophobic glass fiber aerogel felt according to claim 1, characterized in that: In the hot pressing and curing stage of step S4, the composite gel material is transported to the front end of the first cavity in the microwave heating equipment, microwave heating is started, and the microwave start power and the production line belt speed are controlled. The microwave start power can be 1 / 6 to 2 / 3 of the total microwave power.
9. The method for preparing a low-density super-hydrophobic glass fiber aerogel felt according to claim 1, characterized in that: In the aging-super-hydrophobic modification treatment stage of step S5, the aging treatment time is 8h~48h, and the hydrophobic modification time is 4h~24h, the hydrophobic modification temperature is 45℃~60℃, and during the aging treatment and hydrophobic modification treatment process, it is necessary to start the circulation pump to circulate the composite wet gel semi-finished product continuously to promote the full reaction of the composite gel material; wherein the hydrophobic agent is selected from at least one of hexamethyldisilazane, dimethyldiethoxysilane or dimethyldimethoxysilane.
10. The method for preparing a low-density super-hydrophobic glass fiber aerogel felt according to claim 1, characterized in that: In step S6, in the drying process, carbon dioxide is used as the drying medium under supercritical conditions, the temperature in the drying kettle is controlled to be 40°C to 75°C, the pressure is 10Mpa to 18Mpa, and the carbon dioxide flow rate is 2m 3 / h~4m 3 / h, the drying time is 4h to 16h; after drying, an aerogel felt material is obtained, and the volume density of the aerogel felt material is not more than 170 kg / m 3 , the hydrophobicity is not less than 99.6%, and the thermal conductivity is not greater than 0.021 W / (mK).